FAKSI DALAM KONFLIK INTERNAL PARTAI KEADILAN SEJAHTERA DI PROVINSI BALI - Tania Harefa, Nia Rinda; Bandiyah, Bandiyah; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2019)
ABSTRACT   This study aims to offer an overview of the factions of the Partai Keadilan Sejahtera (PKS). The theories used in this study are the Theory of factions by Belloni and Beller. According to Belloni and Beller, the emergence of factions is divided into four, inclauding the differences in values, strategies,economic conditions, and personal loyalty. This study uses descriptive qualitative methods to determine and describe various attitudes and phenomena that exist. The findings of the research conducted are first, factions within PKS internally emerged since the 2004 presidential election known as the keadilan and sejahtera factions. Second, subsequently there was a conflict between the PKS leaders and Fahri Hamzah. Third, one of the effects of the factions that appeared and finally causing conflict was that many cadres and administrators withdrew from PKS. One of the affected areas is the Province of Bali.   Keywords : Factions, Internal Conflict, Impact of Conflict, Partai Keadilan Sejahtera